2018
DOI: 10.1007/jhep05(2018)017
|View full text |Cite
|
Sign up to set email alerts
|

Exact results in 3d $$ \mathcal{N} $$ = 2 Spin(7) gauge theories with vector and spinor matters

Abstract: We study three-dimensional N = 2 Spin(7) gauge theories with N S spinorial matters and with N f vectorial matters. The quantum Coulomb branch on the moduli space of vacua is one-or two-dimensional depending on the matter contents. For particular values of (N f , N S ), we find s-confinement phases and derive exact superpotentials. The 3d dynamics of Spin (7) is connected to the 4d dynamics via KK-monopoles. Along the Higgs branch of the Spin(7) theories, we obtain 3d N = 2 G 2 or SU(4) theories and some of the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

6
0

Authors

Journals

citations
Cited by 9 publications
(26 citation statements)
references
References 32 publications
0
26
0
Order By: Relevance
“…In general, the Coulomb branch is drastically modified and different from the classical picture. In [5], we studied the 3d N = 2 Spin(7) gauge theory with vector and spinor matters. We found that the Coulomb moduli space is one-or two-dimensional depending on the matter contents and also found various s-confinement phases.…”
Section: Jhep03(2019)113mentioning
confidence: 99%
See 3 more Smart Citations
“…In general, the Coulomb branch is drastically modified and different from the classical picture. In [5], we studied the 3d N = 2 Spin(7) gauge theory with vector and spinor matters. We found that the Coulomb moduli space is one-or two-dimensional depending on the matter contents and also found various s-confinement phases.…”
Section: Jhep03(2019)113mentioning
confidence: 99%
“…These were studied in [8,9] for the cases where the theory contains JHEP03(2019)113 only vector matters. In [5], we studied these operators in the 3d N = 2 Spin(7) theory with vector and spinor matters. In these examples, we found that almost all the classical Coulomb branches are lifted and the quantum Coulomb moduli space is described by only a few operators.…”
Section: Coulomb Branch In Spin(n ) Theoriesmentioning
confidence: 99%
See 2 more Smart Citations
“…These were studied in [8,9] for the cases where the theory contains only the vector matters. In [5], we studied these operators in the Spin (7) theory with vector and spinor matters. In these examples, we learned that almost all the classical Coulomb branches are lifted and the quantum Coulomb moduli space is described by only a few operators.…”
Section: Coulomb Branch In Spin(n ) Theoriesmentioning
confidence: 99%